Metafora Romantisisme pada Syair Risalatu Min Tahtil Ma’ Karya Nizar Qabbani (Kajian Balaghah) - Rusna, Dyo; Rohanda, Rohanda; Azzahra, Rachma Aini; Alandira, Palendika (LPPM STKIP PGRI Bandar Lampung, 2024)
This study aims to analyze the metaphor of romanticism in the poem